Active resource allocation design for QoS improvement in wireless broadband interworking networks. (2017) - Kokila, S.; Sivaradje, G.
The key factor to achieve guaranteed quality of service (QoS) and capacity, without increasing the complexity of the layers in heterogeneous broadband wireless network, is through radio resource management. In this paper, an active resource allocation (ARA) scheme is developed to organise the available resource of the interworking ultra-mobile broadband (UMB), worldwide interoperability for microwave access (WiMAX) and wireless local area network (WLAN). The resource provisioning scheme deals with complete partitioning of available radio channels based on prioritising the type of applications, such as real-time and non-real-time. The ARA scheme is validated through OPNET results obtained for the applications such as VoIP, FTP, HTTP and Email. The results are compared with the ARA implemented in Universal Mobile Telecommunication System (UMTS)-WiMAX-WLAN Interworking network and without resource allocation, which unveils the ability of the UMB network and the proposed scheme to provide high QoS satisfaction level by exploiting the overall available resource.